Stereotyped accent judgements in forensic contexts: listener perceptions of social traits and types of behaviour - Paver, Alice; Wright, David; Braber, Natalie; Pautz, Nikolas (Frontiers in Communication, 2025)
This paper reports the findings from a multidisciplinary and cross-institutional Economic and Social Research Council (ESRC) funded project called ‘Improving Voice Identification Procedures’ (IVIP). People harbour stereotypes about particular accents, and those judgements may be brought with them into the legal domain. Considering the potential consequences of accent judgements by witnesses and jurors, this study examines the relationship between ratings for characteristics and the likelihood of acting in certain criminal and non-criminal ways. 180 participants completed an accent judgement task, rating 10 regionally-accented British voices on a range of traits and behaviours using a wider variety of accents, behaviours and criminal offences than previous research. Results indicate that evaluations of perceived characteristics based on accent translate into evaluations of likely behaviours. Non-standard UK regional accents are generally perceived more negatively than a standard one, but not universally; non-English accents elicited more positive trait and behaviour ratings than English accents. Furthermore, although accents evaluated as low-status were generally more likely to behave criminally according to listeners, this varied according to the type of crime. The discussion explores the forensic implications of the relationships between perceived status and criminality, as well as discussing the significance of perceptions of perpetrators of sexual offences when compared to other offence types. We emphasise the need for nuanced understanding of how accents are evaluated when it comes to different crime types.